A geovisual analytics approach for mouse movement analysis. (6th January 2015) - Tahir, Ali; McArdle, Gavin; Bertolotto, Michela
The use of web maps has created opportunities and challenges for map generation and delivery. While volunteered geographic information has led to the development of accurate and inexpensive web maps, the sheer volume of data generated has created spatial information overload. This results in difficulties identifying relevant map features. Geopersonalisation, which adapts map content based on user interests offers a solution to this. The technique is especially powerful when implicit indicators of interest are used as a basis for personalisation. This article describes the design and features of VizAnalysisTools, a suite of tools to visualise and interpret users' implicit interactions with map content. While traditional data mining techniques can be used to identify trends and preferences, visual analytics, in particular geovisual analytics, which assists the human cognition process, has proven useful in detecting interesting patterns. By identifying salient trends, areas of interest on the map become apparent. This knowledge can be used to strengthen the algorithms used for geopersonalisation.